MAINTAINING CULTURAL HERITAGE OF NUSANTARA AND ITS RELATIONS TO THE WORLD HERITAGE - Hakim, Lukmanul (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This writing is about the importance of maintaining the cultural heritage of Nusantara as the effort to maintain the heritage of the world. This writing argues that the culture of Nusantara is the result of the assimilation process of different advanced civilizations of the world such as that of Chinese, Arabs, Persian, Indian, European etc. Each of those civilizations has given a valuable contribution to the development of cultures in Indonesian Archipelago (formerly known as Nusantara). The process of cultural development thus produces a valuable cultural property in the form of buildings such as architectural mosaic and intellectual works such as literary works. Cultural richness consists of two kinds of cultures namely; the culture of material and the culture of thought. These are the two significant cultures which have been shaping the personality of a nation or society. These two kinds of cultures have the positive and noble values that become the driving force for the nation to develop. Thus, to maintain the cultural heritage of Nusantara means to maintain the world heritage as some elements of the heritage of Nusantara are taken from many other nations. To analyze the process of how to maintain the cultural heritage of Nusantara (Indonesia), this writing uses the theory of civilization by Toynbee which is known as the theory of Challenge and Response. The theory is useful to see how one culture can develop and reach high culture and finally can produce the grandeur of civilization.